Implementation of the Information Disclosure Programme at the Communication and Information Office of Minahasa Regency - Thelma Wawointana,; Jeane E. Langkai,; Kezia A. Ashari,; Patriani Supit, (Technium Social Sciences Journal, 2023)
Provision of maximum and open information services to the public will provide satisfaction to the service recipients, especially in receiving information that must be known by the public. This study aims to find out and describe how the implementation of the openness program for information services and documentation management at the Minahasa District Communication and Information Service. In this study using qualitative research methods, the research location of the Minahasa District Communication and Information Office. The results of this study state that the implementation of the information disclosure and documentation program policy at the Minahasa District Communication and Informatics Service has not been implemented properly, especially in access to information and communication, where: 1) There is no comprehensive transparency regarding various information that every community has the right to know that is from various programs related to the community, activities, as well as the budget of the program to be carried out, 2) The government does not clearly know the rules that serve as a reference in the service openness program, 3) There is no comprehensive socialization carried out by the Communication and Information Service to all people are concerned with various programs that will be carried out or are being carried out, and 4) The government does not really understand regarding various information that is excluded.